A impugnação ao cumprimento de sentença, conforme a lei 11.232/2005 - Ribeiro, Flávia Pereira (2008)
The reforms introduced by Law No. 11,232/2005 changed significantly the execution of the judicial settlement. Firstly, the new regulation created a syncretism between cognition and execution, integrating these activities in the same judicial procedure, which no longer ends with a court decision, but with the effective satisfaction of the claimant. Therefore, the creditor that did not receive a due payment may require the immediate employment of the executive means, without the need of bringing a new claim before the court. Secondly, besides that significant simplification, the motion to stay collection filed by the debtor is no longer a form of reaction to the execution of court decision. It was superseded by a new form of defense that takes place within the judicial proceedings, which was denominated impugnação. In addition to those reforms, a number of other modifications in the field of execution of court decisions could also be listed. In view of this new reality, the present study is intended to examine all aspects involving the novel form of reaction of the debtor against an unfair or illegal execution of a court decision, analyzing issues such as (i) the legal nature of impugnação and the results thereof; (ii) the procedure applicable to impugnação; (iii) the possible interference it causes in the normal course of the executive procedures; (iv) the applicable arguments, on both procedure and merit, and the level of cognition that can possibly be reached in each legal hypothesis; (v) the consequences of the court decisions which judge the impugnação and the pertinent remedies; (vi) the possibility of constitution of res judicata and the consequent applicability of rescissory action; and (vii) the coexistence of this new form of defense with other forms of defense which are familiar to the those who work with the Law - the exceção de pré-executividade and the defesa heterotópica. The purpose of this study, therefore, is to elucidate a number of relevant practical and theoretical situations involved in the matter so as to contribute to a correct understanding of the new legal precept impugnação ao cumprimento de sentença